Does knowledge of liver fibrosis affect high-risk drinking behaviour (KLIFAD): an open-label pragmatic feasibility randomised controlled trialResearch in context - Mohsan Subhani; Doyo G. Enki; Holly Knight; Katy A. Jones; Kirsty Sprange; Stefan Rennick-Egglestone; Joanne R. Morling; Andrew Wragg; Clare Hutton; Stephen D. Ryder (EClinicalMedicine, 2023)
Summary: Background: Early identification followed by effective behaviour interventions is pivotal to changing the natural history of alcohol-related liver disease. We examined the feasibility of using transient elastography based advice and alcohol recovery video stories (ARVS) to change drinking behaviour in community alcohol services. Methods: A feasibility randomised control trial (RCT) was conducted in three community alcohol services. Adults 18+ years presenting with a primary alcohol problem were randomised (1:1) to receive either usual care (control group) or usual care and the KLIFAD Intervention, consisting of advice tailored to liver stiffness measure and access to ARVS (intervention group). Data were collected at baseline and six months. To establish definitive trial feasibility, recruitment and retention rates, study procedure safety and extent of effectiveness were measured (Start date: 02.10.2019, End date: 30.11.2022, ISRCTN.com: 16922410). Findings: 382 service users were screened, 184 were randomised (intervention: 93, control: 91), and baseline data were collected for 128 (intervention: 71, control: 59). Six months follow-up data were available in 87 (intervention: 53, control: 34). Intervention compared to the control group had a longer duration of engagement with services (mean difference 8.6 days SD = 18.4), was more likely to complete the allocated treatment program and reduced or stop drinking (54.9% vs 43.9%) and reduce AUDIT category (71.7% vs 61.8%). There were no reported serious adverse reactions, one intervention group participant reported an increase in AUDIT category. Interpretation: Integration of transient elastography in community alcohol services is feasible. It may improve engagement with services, retention in clinical trials and supplement the reduction in self-reported alcohol consumption. A definitive RCT is supported. Funding: National Institute for Health and Care Research (NIHR201146).